Online Word of Mouth as A Channel of Communication in Eulogio “Amang” Rodriguez Institute of Science And Technology (Earist) (International Journal of Scientific Research and Management (IJSRM), 2024)
Leveraging online word of mouth in schools can enhance communication, collaboration, and community building among students, faculty, parents, and other stakeholders, contributing to a more positive and engaging learning environment. Online word of mouth serves as a dynamic and influential communication channel in the digital landscape, offering reach, immediacy, interactivity, and persuasive power. By understanding its characteristics and leveraging its potential, individuals and organizations can effectively communicate, engage with their audience, and achieve their communication objectives in the digital era. In this study sentiment, volume, source credibility, content characteristics, engagement, platform and timing influenced the dynamics, impact, and outcomes of using online word of mouth of Eulogio “Amang’ Rodriguez Institute of Science and Technology (EARIST) students, faculty, parents, and other stakeholders as a channel in communication.